The design and development of a learning strategy to enhance students' engagement in simultaneous equations: An evaluation viewpoint - Jaafaru Aliyu; Sharifah Osman; Jeya Amantha Kumar; Mohd Ridhuan Mohd Jamil (OmniaScience, 2023)
In the 21st century, teaching and learning mathematics courses witness significant expansion and development of technology use, which creates a shift from teacher-centred to student-centred learning engagement. Student engagement (SE) faces many challenges of poor performance and student difficulty in solving simultaneous equations involving indices (SEII), among others. This paper presents an evaluation viewpoint of the learning strategy (LS) with cooperative learning strategy (CLS) and GeoGebra (GG) integration to support SE in SEII. The LS employs the think-pair-share approach and the six (6) principles of learning phases associated with constructivism ideology. The discussion of the preliminary mathematical achievement test (MAT-test) from pre-and post-tests with 41 students who have learned SEII using the developed LS is also presented. Semi-structured interviews were conducted with three experienced lecturers to provide feedback and recommendations on interacting with LS. The themes that emerge from those lecturers include the connection between LS phases, specific material, cooperative activity, playfulness in the discovery process, and thinking. Experts' feedback on the LS's content reasoning and content learning strategy through a questionnaire was tested using Fleiss multi-rater Kappa and showed good inter-rater reliability and agreement between them. The estimated marginal means covariate of the ANCOVA test was then examined, and the results supported the necessity for a learning strategy to be developed. The findings revealed that the LS, with CLS and GG integration, has the potential to be educationally effective in enhancing SE in SEII.